Simultaneous determination of nine lignans using pressurized liquid extraction and HPLC-DAD in the fruits of Schisandra chinensis - Lee, Hee Ju; Kim, Chul Young (ELSEVIER SCI LTD, 2010)
The pressurized liquid extraction and HPLC-DAD was developed for extraction and determination of bioactive lignans in Schisandra chinensis. The efficient PLE conditions employed methanol as extraction solvent, 125 degrees C of extraction temperature, 5 min of static extraction time and only one cycle. A rapid HPLC-DAD method was described for simultaneous determination of nine lignans, including schisandrol A, gomisin J, schisandrol B, tigloylgomisin H, angeloylgomisin H, schisandrin A, gamma-schisandrin, gomisin N and schisandrin C. The extraction efficiency of PLE was observed to be comparable with reflux and sonication. In addition, the contents of nine lignans in S. chinensis from different regions were analysed by PLE and HPLC-DAD method. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: COUNTER-CURRENT CHROMATOGRAPHY; SCHIZANDRA-CHINENSIS; GOMISIN-A; CONSTITUENTS; BAILL; SEPARATION